Modelos de negócios digitais para infoprodutos e os empreendedores digitais - Oliveira-Cunha, Yuri Lazaro de (2024)
This study investigated the digital business models used by entrepreneurs who produce, commercialize, and distribute info-products. Through a qualitative and exploratory approach based on multiple case studies, the characteristics and components of these business models were identified, in addition to exploring the evolution of these digital ventures. The research has both academic and practical relevance. Academically, it thoroughly investigates a digital entrepreneurship phenomenon in an emerging context. Practically, it provides insights that can guide new digital entrepreneurs, especially considering the high global mortality rate of new businesses. The theoretical framework encompassed concepts about the digital business model, digital entrepreneurship, and info-products. Through semi-structured interviews with digital info-product entrepreneurs, we sought to understand their strategies, processes, and adopted business models, as well as the developed digital artifacts. The analysis of the cases indicated a convergence regarding the focus of the models on content production, with partnerships to complement commercialization and distribution activities. At the same time, the motivations, organizational configurations, info-product formats, and challenges faced differed among the analyzed entrepreneurs. The contributions include providing a better understanding of the still poorly explored info-product phenomenon in the context of digital entrepreneurship, bringing information about digital business models for info-products that can guide new entrepreneurs. The study also provides insights for future research on an emerging research field.